VD_FINDINFO Décision / 2024 / 683 vom 24. August 2024 - VD Tribunal cantonal (2024)
INDEMNITÉEN GÉNÉRAL, RÉDUCTIONEN GÉNÉRAL, ADMISSION DE LA DEMANDE, DÉFENSE D'OFFICE | 38 al. 1 LEP, 38 LEP, 135 CPP (CH), 395 let. b CPP (CH)